Method for manufacturing electrode laminate
By covering the electrode surface with oxygen blocking components, the electrolyte is completely cured in an oxygen environment, which solves the problem that the gel electrolyte fails to cure completely, and achieves the manufacturing of large-area electrode laminates and the performance improvement of lithium secondary batteries.
Patent Information
- Application Number
- CN202380056663.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-30
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-11
AI Technical Summary
When manufacturing large-area electrode laminates in an oxygen environment, the gel electrolyte fails to fully cure, resulting in volatilization or contact separation with other electrodes during the battery cell manufacturing process, making it difficult to solve the problems of safety and manufacturing scale.
The electrolyte is blocked from contact with oxygen by coating the electrode surface and covering oxygen-blocking components (such as glass, polypropylene or high-density polyethylene) to completely cure the electrolyte in an oxygen environment.
It is possible to completely cure the gel electrolyte in an oxygen environment to prevent it from evaporating or separation, and to manufacture a large-area electrode laminate, which improves the safety and performance of lithium secondary batteries.
Smart Images

Figure CN119605016A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0109521 filed in the Korean Intellectual Property Office on August 30, 2022, the entire contents of which are incorporated herein by reference. Technical Field
[0004] The present invention relates to a method for manufacturing an electrode laminate. Background Art
[0005] In recent years, with the development of technology and the increase in demand for energy storage systems (ESS), the demand for batteries as energy sources has increased dramatically, and research on batteries that can meet various requirements has been carried out accordingly. In particular, research on lithium secondary batteries that have high energy density and also exhibit excellent life and cycle characteristics as power sources for such devices has been actively carried out.
[0006] Generally, a lithium secondary battery includes a positive electrode, a negative electrode, a separator and an electrolyte inserted between the positive electrode and the negative electrode, etc. As a typical electrolyte for lithium secondary batteries, a liquid electrolyte in which a lithium salt is dissolved in a non-aqueous organic solvent is mainly used. However, the use of such a liquid electrolyte is likely to cause degradation of the electrode material and volatilization of the organic solvent, and also brings concerns about combustion or explosion and leakage caused by increased ambient temperature and the temperature of the battery itself, resulting in low safety.
[0007] Recently, research on various materials or types of solid electrolytes has been actively conducted to overcome the safety issues of liquid electrolytes. In particular, gel electrolytes provide excellent stability and processability, and also have their own gel phase bonding strength, thereby providing advantages such as excellent interface stability between electrodes and electrolytes.
[0008] Meanwhile, gel electrolytes can be prepared by gelling (crosslinking) a composition mixed with a lithium salt, a solvent, a polymerizable monomer, and an initiator at an appropriate temperature for a reasonable time. In this case, when the electrolyte is gelled in an oxygen environment, the gel electrolyte is not completely cured, and as a result, the gel electrolyte volatilizes or contacts other electrodes and separates during the manufacture of the battery cell. When the electrolyte is gelled in a space (such as a glove box) where an oxygen-free environment is set to prevent the above problems from occurring, it is difficult to manufacture a large electrode laminate due to the limitation of the space size.
[0009] Therefore, there is a need for technology to develop a method for manufacturing a large-area electrode laminate by completely curing a gel electrolyte even in an oxygen environment. Summary of the invention
[0010] Technical issues
[0011] One aspect of the present invention provides a method of completely curing a gel electrolyte even in an oxygen environment by blocking contact between the gel electrolyte and oxygen using an oxygen blocking member.
[0012] Technical Solution
[0013] According to one aspect of the present invention, a method for manufacturing an electrode laminate is provided, which includes: preparing an electrode, applying an electrolyte to the electrode, providing an oxygen blocking component on the applied electrolyte, and solidifying the electrolyte immersed in the electrode and the electrolyte applied to the surface of the electrode.
[0014] According to the method for producing the electrode laminate, the electrolyte solution applied to the surface of the electrode can be solidified to form an electrolyte layer on the electrode.
[0015] The oxygen blocking member may include at least one selected from the group consisting of glass, polypropylene (PP), and high-density polyethylene (HDPE).
[0016] The electrolyte may include 5 wt % to 50 wt % of a monomer, 0.01 wt % to 1 wt % of an initiator, and 5 wt % to 30 wt % of a lithium salt.
[0017] The monomer may include at least one selected from the group consisting of ethylene glycol diacrylate, triethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate (ETPTA), bisphenol A ethoxylated dimethacrylate, acrylic acid, carboxyethyl acrylate, methyl cyanoacrylate, ethyl cyanoacrylate, ethyl cyanoethoxyacrylate, cyanoacrylic acid, hydroxyethyl methacrylate, and hydroxypropyl acrylate.
[0018] The initiator may include 2-hydroxy-2-methylpropiophenone (HMPP), 1-hydroxy-cyclohexyl phenyl ketone, benzophenone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, oxy-phenylacetic acid 2-[2-oxo-2-phenyl-acetoxy-ethoxy]-ethyl ester, oxy-phenyl-acetic acid 2-[2-hydroxyethoxy]-ethyl ester, α-dimethoxy-α-phenylacetophenone, 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholine At least one of the group consisting of bis(2,4,6-trimethylbenzoyl)phenyl]-1-butanone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(η5-2,4-cyclopentadien-1-yl)bis[2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl]titanium, 4-isobutylphenyl-4'-methylphenyliodonium hexafluorophosphate and methyl benzoylformate.
[0019] According to the method for producing the electrode laminate, the electrolyte solution may be photocured or thermally cured to form the electrolyte layer.
[0020] According to the method for manufacturing the electrode laminate, the solid content of the electrolyte may be 10% to 60%.
[0021] According to the method for producing an electrode laminate, the viscosity of the electrolyte at 25° C. may be 30 cP or less.
[0022] According to the method for manufacturing the electrode laminate, the thickness of the electrolyte layer may be 10 μm to 200 μm.
[0023] According to the method for manufacturing the electrode laminate, the thickness of the electrode can be 100 μm or less.
[0024] Beneficial effects
[0025] According to the present invention, the electrolyte is solidified by blocking the contact between the electrolyte and oxygen using an oxygen blocking member, so that the gel electrolyte can be completely solidified even in an oxygen environment. Therefore, the gel electrolyte can be prevented from volatilizing or contacting other electrodes and separating during the battery cell manufacturing process.
[0026] In addition, the electrolyte can be solidified while being impregnated to a sufficient depth in the electrode, so even if no additional liquid electrolyte is injected into the electrode laminate in the manufacture of the lithium secondary battery, a reaction occurs uniformly throughout the electrode, thereby improving capacity, output and life characteristics.
[0027] In addition, according to the present invention, the electrolyte does not need to be gelled in a space such as a glove box set up as an oxygen-free environment, and thus, it is possible to manufacture a large-area electrode laminate. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 : is an image showing the surface of the electrode laminate produced in Example 1.
[0029] Figure 2 : is an image showing the surface of the electrode laminate produced in Example 2.
[0030] Figure 3 : is an image showing the surface of the electrode laminate produced in Comparative Example 1.
[0031] Figure 4 : is a graph showing the capacity (mAh)-voltage (V) of the lithium secondary battery manufactured in Example 1 when charged.
[0032] Figure 5 3 is a graph showing the capacity (mAh)-voltage (V) of the lithium secondary battery manufactured in Example 2 when charged.
[0033] Figure 6 : is a graph showing the capacity (mAh)-voltage (V) of the lithium secondary battery manufactured in Comparative Example 1 when charged. DETAILED DESCRIPTION
[0034] The advantages and features of the present invention and methods for implementing the same will be explained by the following embodiments described with reference to the accompanying drawings. However, the present invention can be implemented in different forms and should not be construed as being limited to the embodiments described herein. On the contrary, these embodiments are provided to make the present disclosure fully complete and to fully convey the scope of the present invention to those skilled in the art. In addition, the present invention is limited only by the scope of the claims. Throughout the specification, the same reference numerals represent the same elements.
[0035] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the meanings commonly understood by ordinary technicians in the field to which the invention belongs. Unless clearly and specifically defined, terms defined in commonly used dictionaries will not be ideally or over-interpreted.
[0036] The terms used herein are not intended to limit the inventive concept but to illustrate the embodiments. Unless the context clearly indicates otherwise, the singular form used herein also includes the plural form. The meaning of "including" and / or "comprising" used in this specification does not exclude the presence or addition of other components other than the components.
[0037] In the present specification, when an element “includes” components, unless explicitly described to the contrary, it may mean that the element does not exclude other components but may further include other components.
[0038] In this specification, the description "A and / or B" means A or B, or A and B.
[0039] As used herein, "%" means % by weight unless otherwise specified.
[0040] The viscosity used herein may be measured using a viscometer, specifically, a Brookfield viscometer (DV-IIPRO Viscometer, Brookfield) as a viscometer at 25° C., 50% relative humidity (RH) and a frequency of 30 Hz.
[0041] Hereinafter, the present invention will be described in more detail.
[0042] A method for manufacturing an electrode laminate includes preparing an electrode, applying an electrolyte to the electrode, providing an oxygen blocking member on the applied electrolyte, and curing the electrolyte impregnated inside the electrode and the electrolyte applied to the surface of the electrode.
[0043] When the electrolyte is gelled in an oxygen environment, the gel electrolyte is not completely solidified, and as a result, the gel electrolyte volatilizes or contacts other electrodes and separates during the process of manufacturing the battery cell. When the electrolyte is gelled in a storage space (such as a glove box) with an oxygen-free environment to prevent the above problems from occurring, it limits the space size and makes it difficult to manufacture a large electrode laminate.
[0044] The present inventors have made an effort to overcome the above-mentioned problems and have found that the gel electrolyte can be completely cured even in an oxygen environment by blocking the contact between the electrolyte and oxygen using an oxygen blocking member, thereby completing the present invention.
[0045] Hereinafter, the method for manufacturing the electrode laminate of the present invention will be described step by step in more detail.
[0046] <Method for producing electrode laminate>
[0047] (1) Prepare electrodes
[0048] The method for producing an electrode laminate of the present invention starts with preparing an electrode for a lithium secondary battery. In this case, the electrode may be a positive electrode or a negative electrode.
[0049] The electrode includes a current collector and an electrode active material layer. In this case, the electrode active material layer may be formed on the current collector.
[0050] The current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used as the current collector.
[0051] In addition, the electrode active material layer can be a positive electrode active material layer containing a positive electrode active material or a negative electrode active material layer containing a negative electrode active material.
[0052] As the positive electrode active material, positive electrode active materials known in the art can be used without limitation. For example, lithium cobalt-based oxides, lithium nickel-based oxides, lithium manganese-based oxides, lithium iron phosphate, lithium nickel manganese cobalt-based oxides, or combinations thereof can be used. Specifically, as the positive electrode active material, LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiFePO4, and LiNi a Mn b Co c O2 (where 0 < a, b, c < 1), etc., but the positive electrode active material is not limited thereto.
[0053] The negative electrode active material can be, for example, one or at least two selected from the group consisting of the following materials: natural graphite; artificial graphite; carbonaceous materials; lithium-containing titanium composite oxide (LTO); metal (Me): Si, Sn, Li, Zn, Mg, Cd, Ce, Ni, or Fe; alloys formed by the metal (Me); oxides formed by the metal (Me) (MeO x ); and composites of the metal (Me) and carbon.
[0054] Meanwhile, in addition to the positive electrode active material and the negative electrode active material, the electrode active material layer can also contain a conductive material and a binder.
[0055] The conductive material is a component for further improving the conductivity of the active material. The conductive material is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. As the conductive material, for example, the following conductive materials can be used, such as: graphite; carbon black, such as acetylene black, ketjen black, channel black, furnace black, lamp black or thermal black; conductive fiber, such as carbon fiber or metal fiber; metal powder, such as carbon fluoride powder, aluminum powder and nickel powder; conductive whisker, such as zinc oxide whisker and potassium titanate whisker; conductive metal oxide, such as titanium oxide; or polyphenylene derivatives. Specific examples of commercially available conductive materials can include acetylene black series, such as products manufactured by Chevron Chemical, Denka black manufactured by Denka Singapore Private Limited, products manufactured by Gulf Oil, Ketjen black, EC series manufactured by Armak, Vulcan XC-72 manufactured by Cabot, and Super P manufactured by Timcal.
[0056] The binder is a component that helps the active material to bind to the conductive agent and the like and to bind to the collector. Examples of the binder may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber and various copolymers thereof.
[0057] The thickness of the electrode of the present invention can be less than 100 μm, specifically 20 μm to 100 μm, and more specifically 50 μm to 100 μm. When the thickness of the electrode meets the above numerical range, the electrolyte described later can be solidified when immersed in the electrode to a sufficient depth, so even if no additional liquid electrolyte is injected into the electrode laminate in the manufacture of the lithium secondary battery, the reaction will occur uniformly on the entire electrode, thereby improving the capacity, output and life characteristics.
[0058] (2) Apply the electrolyte to the electrode
[0059] Next, the application of the electrolyte solution to the electrodes will be described.
[0060] The electrolyte of the present invention may include a monomer, an initiator, a lithium salt and a solvent.
[0061] A monomer is a material that can form a gel electrolyte through a polymerization reaction.
[0062] For example, the monomer may be at least one selected from the group consisting of ethylene glycol diacrylate, triethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate (ETPTA), bisphenol A ethoxylated dimethacrylate, acrylic acid, carboxyethyl acrylate, methyl cyanoacrylate, ethyl cyanoacrylate, ethyl cyanoethoxyacrylate, cyanoacrylic acid, hydroxyethyl methacrylate, hydroxypropyl acrylate, derivatives thereof, or combinations thereof, but is not limited thereto.
[0063] The content of the monomer may be 5 to 50 parts by weight, specifically 5 to 30 parts by weight, and more specifically 5 to 20 parts by weight relative to 100 parts by weight of the electrolyte. When the content of the monomer is within the above range, sufficient cross-linking reaction occurs between the monomers, and therefore, an electrolyte layer having a specific thickness range can be manufactured.
[0064] The initiator is a material used to form active free radicals, thereby inducing the polymerization reaction of the monomer. Specifically, the initiator can form free radicals by light decomposition such as UV at room temperature (5°C to 30°C), or by thermal decomposition at 30°C to 100°C, thereby initiating the free radical polymerization reaction of the monomer.
[0065] The initiator may include at least one selected from the group consisting of a photocuring agent and a thermal curing agent.
[0066] When the initiator is a photocuring agent, the initiator may include 2-hydroxy-2-methylpropiophenone (HMPP), 1-hydroxy-cyclohexyl phenyl ketone, benzophenone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, oxy-phenylacetic acid 2-[2-oxo-2-phenyl-acetoxy-ethoxy]-ethyl ester, oxy-phenyl-acetic acid 2-[2-hydroxyethoxy]-ethyl ester, α-dimethoxy-α-phenylacetophenone, 2-benzyl-2-(dimethylamino)-1-[4 -(4-morpholinyl)phenyl]-1-butanone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(η5-2,4-cyclopentadien-1-yl)bis[2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl]titanium, 4-isobutylphenyl-4'-methylphenyliodonium hexafluorophosphate and methyl benzoylformate.
[0067] When the initiator is a thermal curing agent, the initiator may include at least one selected from the group consisting of benzoyl peroxide, acetyl peroxide, dilauroyl peroxide, di-tert-butyl peroxide, tert-butyl peroxy-2-ethylhexanoate, isopropylbenzene hydroperoxide, hydrogen peroxide, 2,2'-azobis(2-cyanobutane), 2,2'-azobis(methylbutyronitrile), 2,2'-azobisisobutyronitrile (AIBN) and 2,2'-azobis(dimethylvaleronitrile) (AMVN).
[0068] Relative to 100 parts by weight of the electrolyte, the content of the initiator can be 0.01 to 1 parts by weight, specifically 0.05 to 0.5 parts by weight, and more specifically 0.06 to 0.1 parts by weight. When the content of the initiator is within the above range, an active cross-linking reaction can occur between the monomers to form an electrolyte layer with a uniform thickness, and the polymerization rate in the electrolyte can be controlled, thereby preventing the unreacted initiator from remaining and adversely affecting the battery performance.
[0069] Lithium salts are used as media for transporting ions in lithium secondary batteries.
[0070] Lithium salt is a material that is easily soluble in gel electrolyte, and may include, for example, a material selected from the group consisting of LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , a single substance or a mixture of two or more substances from the group consisting of LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium 4-phenylborate and imide, but not limited thereto.
[0071] The content of the lithium salt may be 5 to 30 parts by weight, specifically 10 to 20 parts by weight, and more specifically 10 to 15 parts by weight relative to 100 parts by weight of the electrolyte. When the content of the lithium salt is within the above range, the solidified electrolyte may have sufficient ion conductivity.
[0072] The solvent is used to dissolve the above-mentioned monomers, initiator and lithium salt.
[0073] The solvent is a commonly used solvent in secondary batteries, for example, ether, ester (acetate, propionate), amide, linear carbonate or cyclic carbonate, nitrile (acetonitrile, SN, etc.) can be used alone, or at least two of them can be mixed and used in combination.
[0074] In particular, generally, a carbonate-based solvent containing a carbonate compound which is a cyclic carbonate, a linear carbonate or a mixture thereof can be used.
[0075] The specific example of cyclic carbonate compound includes a compound selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate and its halogenated compound or a mixture of at least two compounds. In addition, as a specific example of linear carbonate compound, a compound selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC) and ethyl propyl carbonate (EPC) or a mixture of at least two compounds can be used, but embodiments of the present invention are not limited thereto.
[0076] Particularly, among carbonate solvents, propylene carbonate and ethylene carbonate as cyclic carbonates are preferably used because they are high-viscosity organic solvents and have a high dielectric constant, thereby satisfactorily dissociating the lithium salts in the electrolyte. When such cyclic carbonates are mixed in an appropriate proportion with a linear carbonate having a low viscosity and a low dielectric constant such as ethyl methyl carbonate, diethyl carbonate or dimethyl carbonate and used, an electrolyte with high electrical conductivity can be prepared. Therefore, it is more preferred to use such a mixture.
[0077] In addition, as the ester in the solvent, one compound or a mixture of at least two selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone can be used, but the embodiments of the present invention are not limited thereto.
[0078] The solid content of the electrolyte may be 10% to 60%, specifically 15% to 50%, and more specifically 15% to 35%. When the solid content of the electrolyte satisfies the above numerical range, the electrolyte may have a viscosity that can be applied to the electrode active material layer. In addition, when the electrolyte solidifies, the solvent is easily removed, and therefore, side reactions due to residual solvents or reduction in the mechanical strength of the electrolyte layer can be prevented.
[0079] At 25° C., the viscosity of the electrolyte may be 30 cP or less, specifically 5 cP to 30 cP, and more specifically 10 cP to 20 cP. When the viscosity of the electrolyte satisfies the above numerical range, the electrolyte can be solidified while being immersed in the electrode to a sufficient depth, so that even if no additional liquid electrolyte is injected into the electrode laminate in the manufacture of the lithium secondary battery, the reaction will occur uniformly over the entire electrode, thereby improving capacity, output, and life characteristics.
[0080] As the electrolyte coating method, a common coating method can be used, for example, bar coating, spin coating, roller coating, slot die coating, hand coating, spray coating, etc., and one method or a combination of two or more methods can be used.
[0081] (3) Install an oxygen blocking component on the applied electrolyte
[0082] Then, an oxygen blocking member is provided on the electrolyte applied to the electrode. The electrolyte can be covered by the oxygen blocking member, thereby blocking contact between the electrolyte and oxygen.
[0083] The oxygen blocking component may be insoluble in the solvent, thereby effectively blocking the contact between the electrolyte and oxygen. Specifically, the oxygen blocking component may be insoluble in the organic solvent.
[0084] For example, the oxygen blocking member may include at least one selected from the group consisting of glass, polypropylene (PP), and high-density polyethylene (HDPE), but is not limited thereto.
[0085] The thickness of the oxygen blocking member may be 100 μm to 2000 μm, specifically 100 μm to 500 μm, more specifically 100 μm to 200 μm. When the thickness of the oxygen blocking member satisfies the above numerical range, contact between the electrolyte and oxygen is blocked, so the electrolyte can be completely solidified.
[0086] (4) Solidify the electrolyte impregnated in the electrode and the electrolyte applied to the electrode surface
[0087] Then, the electrolyte impregnated inside the electrode and the electrolyte applied on the surface of the electrode are solidified. In this case, the solidification of the electrolyte applied on the surface of the electrode can form an electrolyte layer on the electrode.
[0088] The curing of the electrolyte may be photocuring or thermal curing. Specifically, the curing of the electrolyte may involve crosslinking the monomers contained in the electrolyte by emitting ultraviolet (UV) rays or applying heat to the electrolyte covered by the oxygen blocking component. The electrolyte is cured when the contact between the electrolyte and oxygen is blocked by the oxygen blocking component, thereby preventing the electrolyte from volatilizing or preventing the electrolyte layer from contacting other electrodes and separating.
[0089] The electrolyte layer of the present invention may include a polymer matrix formed by cross-linking a monomer and an initiator and a lithium salt impregnated into the polymer matrix. In this case, the electrolyte layer contains the lithium salt and thus may have ion conductivity.
[0090] The curing degree of the electrolyte layer may be 93% to 100%, specifically 95% to 100%, and more specifically 98% to 100%. When the curing degree of the electrolyte layer satisfies the above range, the electrolyte layer can be formed on the active material layer to have a uniform thickness, and the problem of separation of the electrolyte layer from the active material layer can be prevented.
[0091] The thickness of the electrolyte layer may be 10 μm to 200 μm, specifically 10 μm to 150 μm, and more specifically 20 μm to 80 μm. When the thickness of the electrolyte layer satisfies the above numerical range, the electrolyte layer can be prevented from being separated from the active material layer, positive ions (Li+) as ion carriers can easily pass through, and the performance degradation associated with the total volume of the lithium secondary battery can be minimized.
[0092] After the solidification of the electrolyte is completed, the oxygen blocking member provided on the electrolyte layer may be removed.
[0093] <Method for manufacturing lithium secondary battery>
[0094] Hereinafter, a method for manufacturing a lithium secondary battery of the present invention will be described.
[0095] The lithium secondary battery of the present invention includes an electrode assembly.
[0096] According to an embodiment of the present invention, an electrode assembly may be manufactured by arranging an electrode laminate having an electrolyte layer formed thereon and an electrode having no electrolyte layer formed thereon to be in contact with each other. In this case, the electrode laminate is as described above.
[0097] For example, the electrode assembly of the present invention can be manufactured by arranging an electrode laminate including a negative electrode and an electrolyte layer formed on the negative electrode and a positive electrode on which an electrolyte layer is not formed to contact each other. Alternatively, the electrode assembly of the present invention may include an electrode laminate including a positive electrode and an electrolyte layer formed on the positive electrode and a negative electrode without an electrolyte layer formed. In this case, the electrolyte layer may be disposed between the positive electrode and the negative electrode.
[0098] According to another embodiment of the present invention, in an electrode assembly, a plurality of the above-mentioned electrode laminates may be manufactured by arranging electrolyte layers to be in contact with each other. Forming the electrode assembly in this manner may improve electrical insulation, thereby enabling stable charging and discharging of the battery.
[0099] The lithium secondary battery of the present invention may not include a separator disposed between the positive electrode and the negative electrode in a typical lithium secondary battery. Specifically, the electrolyte layer included in the electrode laminate of the present invention may be disposed between the positive electrode and the negative electrode, and thus may function as a typical separator.
[0100] In addition, the lithium secondary battery of the present invention may not contain the liquid electrolyte injected when manufacturing a normal lithium secondary battery. Specifically, the electrolyte of the present invention described above can be solidified when impregnated to a sufficient depth in the electrode, and thus can function as a normal liquid electrolyte.
[0101] The lithium secondary battery of the present invention can be manufactured by placing the above-mentioned electrode assembly in a cylindrical battery case or a square battery case and sealing the case. The battery case can be a battery case commonly used in the art, and there is no limitation on its shape according to the use of the battery, for example, it can be cylindrical, square, pouch or coin-shaped, but not limited thereto.
[0102] The lithium secondary battery of the embodiment of the present invention can be used as a battery cell used as a power source for small devices, and can also be preferably used as a unit cell in a medium-to-large battery module including a plurality of battery cells. Preferred examples of medium-to-large devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems (ESS).
[0103] Hereinafter, the present invention will be described in more detail by specific embodiments. However, the embodiments shown below are only exemplified for understanding the present invention, and the scope of the inventive concept is not limited thereto. For those skilled in the art, it is obvious that various modifications and changes can be made within the scope of the present invention and within the technical scope, and such modifications and changes fall within the scope of the claims included herein.
[0104] Examples and Comparative Examples
[0105] Example 1
[0106] (1) Preparation of electrode laminate
[0107] A 10 μm thick copper (Cu) metal film was prepared as a negative electrode current collector, and a 70 μm thick negative electrode active material layer containing artificial graphite as a negative electrode active material was prepared on one side of the copper metal film, thereby preparing a negative electrode with a total thickness of 80 μm.
[0108] The monomer, initiator and lithium salt were dissolved in a solvent of ethylene carbonate (EC) and propylene carbonate (PC) at a volume ratio of 5:5 at a weight ratio of 3.98:0.04:5.98 to prepare an electrolyte. In this case, the solid content of the electrolyte was 25% and the viscosity at 25° C. was 15 cP.
[0109] The prepared electrolyte was applied to the active material layer, and the applied electrolyte was covered with a polypropylene film. Then, the polypropylene film was irradiated with ultraviolet light having a wavelength of 556 nm for 1 minute to solidify the electrolyte. After the electrolyte was solidified, the polypropylene film was removed, and finally an electrode laminate having an electrolyte layer formed on the electrode active material layer was obtained. In this case, the thickness of the electrolyte layer was 40 μm.
[0110] (2) Manufacturing of lithium secondary batteries
[0111] Prepare Li(Ni 0.8 Mn 0.1 Co 0.1 )02 as a 60μm positive electrode with positive electrode active material.
[0112] The electrolyte layer of the prepared electrode laminate was brought into contact with the positive electrode to prepare an electrode assembly.
[0113] The electrode assembly is stored in a battery case and sealed to manufacture a lithium secondary battery.
[0114] Example 2
[0115] Except that a glass plate was used instead of the polypropylene film, an electrode laminate was produced in the same manner as in Example 1. In this case, the thickness of the electrolyte layer was 30 μm.
[0116] A lithium secondary battery was manufactured in the same manner as in Example 1 except that the above-mentioned electrode laminate was used.
[0117] Comparative Example 1
[0118] Except that the electrolytic solution was solidified without covering with a polypropylene film, an electrode laminate was produced in the same manner as in Example 1. In this case, the thickness of the electrolyte layer was 10 μm.
[0119] A lithium secondary battery was manufactured in the same manner as in Example 1 except that the above-mentioned electrode laminate was used.
[0120] Experimental Example 1—Evaluation of the coating properties of the electrolyte layer
[0121] The surfaces of the electrode laminates prepared in Examples 1 and 2 and Comparative Example 1 were photographed and shown in FIG. Figures 1 to 3 .
[0122] Specifically, Figure 1 is an image showing the surface of the electrode laminate produced in Example 1, Figure 2 is an image showing the surface of the electrode laminate produced in Example 2, Figure 3 : is an image showing the surface of the electrode laminate produced in Comparative Example 1.
[0123] Furthermore, the surface of the electrode laminate was observed with naked eyes to determine whether the electrolyte layer was separated or floated from the active material layer, as shown in Table 1 below.
[0124] X: No separation or floating
[0125] O: Separation or floating observed
[0126] [Table 1]
[0127] Separation or floating of the electrolyte layer Example 1 X Example 2 X Comparative Example 1 O
[0128] As shown in Table 1 and Figures 1 to 3 As shown, in Comparative Example 1 in which the oxygen blocking member was not used during the electrolyte solidification process, unlike Examples 1 and 2 in which the oxygen blocking member was used during the electrolyte solidification process, separation or floating of the electrolyte layer and the active material layer included in the electrode laminate was observed.
[0129] Experimental Example 2 - Evaluation of the operation of lithium secondary batteries
[0130] In order to evaluate whether the lithium secondary batteries manufactured in Examples 1 and 2 and Comparative Example 1 are operable, a capacity (mAh)-voltage (V) graph was measured when the battery was charged using a Biologic SP-300. The measurement results are shown in the following Figures 4 to 6 Each one.
[0131] Figure 4 is a graph of capacity (mAh)-voltage (V) when charging the lithium secondary battery manufactured in Example 1, Figure 5 is a graph of capacity (mAh)-voltage (V) when charging the lithium secondary battery manufactured in Example 2, Figure 6 This is a graph of capacity (mAh)-voltage (V) of the lithium secondary battery manufactured in Comparative Example 1 when charged.
[0132] like Figures 4 to 6 As shown, in Comparative Example 1 in which the oxygen blocking member was not used during the electrolyte solidification process, an increase in the voltage value of the battery during charging was observed without an increase in the capacity of the battery. This indicates that in Comparative Example 1, the electrolyte layer acting as a separator was separated from the active material layer, and thus the lithium secondary battery was not charged.
[0133] On the other hand, in Examples 1 and 2, in which an oxygen blocking member was used during the solidification of the electrolyte, an increase in the voltage value of the battery during charging was observed along with an increase in the capacity of the battery. This indicates that in Examples 1 and 2, the electrolyte layer serving as a separator was not separated from the active material layer, and therefore the battery was charged normally.
Claims
1. A method for manufacturing an electrode laminate, the method comprising: Prepare electrodes; applying an electrolyte onto the electrode; providing an oxygen blocking member on the coated electrolyte; and The electrolyte impregnated in the electrode and the electrolyte applied on the surface of the electrode are solidified.
2. The method of claim 1, wherein: The electrolyte solution applied onto the surface of the electrode is solidified to form an electrolyte layer on the electrode.
3. The method of claim 1, wherein: The oxygen blocking member includes at least one selected from the group consisting of glass, polypropylene (PP), and high-density polyethylene (HDPE).
4. The method of claim 1, wherein: The electrolyte includes 5 wt % to 50 wt % of a monomer, 0.01 wt % to 1 wt % of an initiator, and 5 wt % to 30 wt % of a lithium salt.
5. The method of claim 4, wherein: The monomer comprises at least one selected from the group consisting of ethylene glycol diacrylate, triethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate (ETPTA), bisphenol A ethoxylated dimethacrylate, acrylic acid, carboxyethyl acrylate, methyl cyanoacrylate, ethyl cyanoacrylate, ethyl cyanoethoxyacrylate, cyanoacrylic acid, hydroxyethyl methacrylate and hydroxypropyl acrylate.
6. The method of claim 4, wherein: The initiator comprises 2-hydroxy-2-methylpropiophenone (HMPP), 1-hydroxy-cyclohexyl phenyl ketone, benzophenone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, oxy-phenylacetic acid 2-[2-oxo-2-phenyl-acetoxy-ethoxy]-ethyl ester, oxy-phenyl-acetic acid 2-[2-hydroxyethoxy]-ethyl ester, α-dimethoxy-α-phenylacetophenone, 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)- )phenyl]-1-butanone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(η5-2,4-cyclopentadien-1-yl)bis[2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl]titanium, 4-isobutylphenyl-4'-methylphenyliodonium hexafluorophosphate and methyl benzoylformate.
7. The method of claim 1, wherein: The electrolyte solution is photocured or thermally cured to form the electrolyte layer.
8. The method of claim 1, wherein: The solid content of the electrolyte is 10% to 60%.
9. The method of claim 1, wherein: The electrolyte has a viscosity of 30 cP or less at 25°C.
10. The method of claim 1, wherein: The electrolyte layer has a thickness of 10 μm to 200 μm.
11. The method of claim 1, wherein: The thickness of the electrode is 100 μm or less.
Citation Information
Patent Citations
In-wheel motor for consistent and efficient assembly
KR1020220109521A